The Economics of a Successful Raccoon Rabies Elimination Program on Long Island, New York. - Julie L Elser; Laura L Bigler; Aaron M Anderson; Joanne L Maki; Donald H Lein; Stephanie A Shwiff (Public Library of Science (PLoS), 2016)
Raccoon rabies is endemic in the eastern U.S.; however, an epizootic had not been confirmed on Long Island, New York until 2004. An oral rabies vaccination (ORV) program was initiated soon after the first rabies-positive raccoon was discovered, and continued until raccoon rabies was eliminated from the vaccination zone. The cost-effectiveness and economic impact of this rabies control program were unknown. A public health surveillance data set was evaluated following the ORV program on Long Island, and is used here as a case study in the health economics of rabies prevention and control efforts. A benefit-cost analysis was performed to determine the cost-effectiveness of the program, and a regional economic model was used to estimate the macroeconomic impacts of raccoon rabies elimination to New York State. The cost of the program, approximately $2.6 million, was recovered within eight years by reducing costs associated with post-exposure prophylaxis (PEP) and veterinary diagnostic testing of rabies suspect animals. By 2019, the State of New York is projected to benefit from the ORV program by almost $27 million. The benefit-cost ratio will reach 1.71 in 2019, meaning that for every dollar spent on the program $1.71 will be saved. Regional economic modeling estimated employment growth of over 100 jobs and a Gross Domestic Product (GDP) increase of $9.2 million through 2019. This analysis suggests that baiting to eliminate rabies in a geographically constrained area can provide positive economic returns.